2019
DOI: 10.1186/s40814-019-0392-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled feasibility trial to evaluate local heat preconditioning on wound healing after reconstructive breast surgery: the preHEAT trial

Abstract: ObjectivepreHEAT was a randomised controlled feasibility trial to determine how best to measure skin necrosis in breast reconstruction to inform the design of a larger multicentre trial.BackgroundMastectomy skin flap necrosis (MSFN) is a serious complication resulting in prolonged wound healing. Local heat preconditioning of the MSF before surgery has been shown to reduce skin necrosis in immediate breast reconstruction patients (IBR).MethodpreHEAT was a single-centre, randomised control two-arm single-blind p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Several studies have con rmed that local heating of the skin can signi cantly improve tissue survival. 24,25 The protective effects observed in these studies are thought to be due to the upregulation of HSP70 and HSP32 expression induced by high temperatures. In addition, Mehta et al 11 heated the skin of breast cancer patients in skin-sparing mastectomy and found that HPC could reduce skin necrosis and duration of hospital stay.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have con rmed that local heating of the skin can signi cantly improve tissue survival. 24,25 The protective effects observed in these studies are thought to be due to the upregulation of HSP70 and HSP32 expression induced by high temperatures. In addition, Mehta et al 11 heated the skin of breast cancer patients in skin-sparing mastectomy and found that HPC could reduce skin necrosis and duration of hospital stay.…”
Section: Discussionmentioning
confidence: 96%
“…Other technical advances have contributed to the trend towards prepectoral IBBR in smaller, yet interesting ways. Several techniques have been described to increase the survival rate and tissue quality of mastectomy flaps; for instance, there is the use of local heat preconditioning [ 92 , 93 ] or hyperbaric oxygen therapy [ 94 ]. Furthermore, the development and clinical implication of intraoperative indocyanine green angiography (ICG) for the real time visualization of tissue perfusion has been another crucial step toward perfecting prepectoral IBBR [ 95 ].…”
Section: Further Technical Developmentsmentioning
confidence: 99%
“…A critical mass of researchers, academics clinicians, and patients in the UK have undertaken a wide range of innovative trials in pressure ulcers, 26,27 leg ulcers, [28][29][30] burns, 31 and other types of wounds. [32][33][34][35][36][37] The Tissue Viability Society created the WReN (https://woundsrn.org/) in 2015 to provide an interprofessional cross-speciality forum where people may share their knowledge, expertise, and insights regarding wound trials and research. The WReN offers opportunities to people from diverse backgrounds to further develop their knowledge and expertise in conducting high-quality wound trials and research regardless of their levels of expertise.…”
Section: The Wounds Research Networkmentioning
confidence: 99%